Mineralocorticoid receptor antagonism in acutely decompensated chronic heart failure - Ferreira, J. (2013)
Spironolactone was likely to provide faster congestion relief. -------------------------------------------------------------------------------- Abstract Background/objectives Mineralocorticoid receptor antagonist (MRA) use in acutely decompensated chronic heart failure (ADCHF) may improve congestion through diuretic effect and prevent neurohormonal activation. We aimed to evaluate the clinical effect and safety of spironolactone in ADCHF. Methods Prospective, experimental, single-center, and single-blinded trial. Patients were treated with: standard ADCHF therapy or oral spironolactone 50–100 mg/d plus standard ADCHF therapy. Results During a 1 year period, 100 patients were enrolled, 50 included in the treatment group. Mean (SD) spironolactone dose (mg) at day 1 was 94.5 ± 23.3 and at day 3 was 62.7 ± 24.3. Worsening renal function (increase in pCr ≥ 0.3 mg/dL from day 1 to day 3) was more likely to occur in control group (20% vs. 4%; p = 0.038), serum potassium did not differ between groups, and plasma NTproBNP had a significant decrease in spironolactone group at day 3 (median [IQR], 2488 [4579] vs. 1555 [1832]; p = 0.05). Furthermore, a greater proportion of patients in the treatment group were free of congestion at day 3: less edema, rales, jugular venous pressure (JVP) and orthopnea (all, p < 0.05). In addition, a significantly higher proportion of patients were on oral furosemide at day 3 (44% vs. 82%; p < 0.001). Conclusions Our study supports the safety of high dose spironolactone in ADCHF and suggests a positive impact in the resolution of congestion. The important findings of our pilot study need to be confirmed in larger trials.